Normal Strength Steel Fiber Reinforced Concrete Subjected to Explosive Loading - Yusof, Mohammed Alias; Norazman, Norazman; Ariffin, Ariffin; Mohd Zain, Fauzi; Risby, Risby; Ng, CP (International Journal of Sustainable Construction Engineering and Technology, 2011)
This paper presents the results of an experimental investigation on the behavior of plain reinforced concrete and Normal strength steel fiber reinforced concrete panels (SFRC) subjected to explosive loading. The experiment were performed by the Blast Research Unit Faculty of Engineering, University Pertahanan Nasional Malaysia A total of 8 reinforced concrete panels of 600mm x 600mm x 100mm were tested. The steel fiber reinforced concrete panels incorporated three different volume fraction, 0.5%, 1.0%, and 1.5% of hooked end steel fibers. The panels were subjected to explosive loading generated by the detonation of 1kg of explosive charge located at a 0.6m standoff. This investigation indicates that the steel fiber reinforced concrete panel containing of 1.5% volume fraction gave the best performance under explosive loading.